Inverse Scattering Method Design of Regrowth-Free Single-Mode Semiconductor Lasers Using Pit Perturbations for Monolithic Integration - Kevin Shortiss; Mohamad Dernaika; Ludovic Caro; Masoud Seifikar; Frank H. Peters (IEEE Photonics Journal, 2018)
An inverse scattering method is used to design regrowth-free single-mode lasers, using etch depth insensitive pits as perturbations in the laser cavity. These pit perturbations are circular holes etched into the waveguide of each laser to a depth 0.8 $μ \text{m}$ below the quantum wells in the laser material, and are used in place of the etch depth sensitive slots more commonly implemented for optical feedback in photonic integrable lasers. We compare the number of these pit perturbations required to achieve the target wavelength of the devices, and report strongly single mode lasers (greater than 40 dB). Devices were then designed to lase at wavelengths between 1545 nm and 1565 nm, to demonstrate the wavelength accuracy of the designs. Thermal tuning was used to tune device wavelength over 2 nm, while maintaining side mode suppression ratios greater than 30 dB.